Pengembangan Yogurt Bunga Telang (Clitoria ternatea L.) menggunakan Pemanis dan Penstabil: Studi Sensoris dan Fisikokimia - Indah Aprianti; Robby Najini (Sinteza, 2025)
Yogurt is a fermented dairy product typically produced using lactic acid bacteria such as Lactobacillus bulgaricus and Streptococcus thermophilus. It is widely recognized for its health benefits, particularly in supporting gut microbiota balance. In recent years, incorporating natural ingredients into yogurt formulations has gained increasing attention, as consumers seek functional foods with added health value. One such ingredient is telang flower, which has been recognized for its richness in antioxidants and anthocyanins. Moreover, it contains polyphenolic compounds like catechins, which are associated with improved metabolic activity and increased fat oxidation, potentially supporting weight control. Ongoing innovations in yogurt development aim to enhance its flavor, texture, and stability, often by incorporating sweeteners and thickening agents. This study aimed to evaluate the sensory properties and consumer acceptability of telang flower yogurt formulated with varying concentrations of natural sweetener (honey) and thickening agent/stabilizer (carboxymethyl cellulose, CMC), and to characterize the physical and chemical attributes of the optimum formula. Four formulations were developed using different concentrations of honey (0%, 10%, 15%, and 20%) and CMC (0%, 1%, 1.5%, and 2%). Formulation FIV, consisting of 20% honey and 2% CMC, achieved the highest level of preference among all tested variants. A vibrant purple color, dense texture, pleasantly acidic aroma, and well-balanced sweetness contributed to its superior sensory profile. This formula exhibited favorable physicochemical characteristics, with a pH of 4.34 and a viscosity of 1910 cP. Increasing honey and CMC concentrations were found to improve both consumer acceptability and the overall sensory.